Analisis Fundamental Makro, Struktur Kepemilikan Terhadap Nilai Perusahaan, Manajemen Laba, Kinerja Keuangan dan Karakteristik Perusahaan sebagai Variable Intervaning pada Perusahaan Sektor Plastik dan Kemasan Bursa Efek Indonesia Tahun 2013-2022 - Neto, Angelique Michella; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to determine and analyze the relationship between macro fundamentals, ownership structure, earnings management, financial performance and company characteristics on company value. The sample for this research is 3 plastic and packaging sector companies listed on the Indonesia Stock Exchange for the 2013-2022 period. The data analysis technique in this research uses smartPLS 4 software. The macro fundamentals measured include inflation, exchange rates, interest rates and gross domestic product. The ownership structure includes institutional, foreign, public, government and managerial ownership. Profit management is measured through net profit margin, ROE, and DAR, while financial performance is measured through sales, receivables turnover, and ROA. Company characteristics are measured by the number of board of directors, commissioners, audit committee, size and age of the company. Company value is measured through closing price, EPS, shares, and Tobins Q. The research results show that macro fundamentals have a significant effect on company value, ownership structure, earnings management, financial performance, and company characteristics. Ownership structure also has a significant influence on earnings management, financial performance, company characteristics and company value. In addition, earnings management, financial performance and company characteristics have a significant influence on company value.